PENGARUH PEMBERIAN SARI KURMA (Phoenix dactylifera) TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL - Elmarossa Dinda Sephia (Jurnal Medika Hutama, 2020)
Anemia in pregnant women is a problem that often occurs in Indonesia. Anemia can occur at any age. In Indonesia, the prevalence of anemia is still high, the incidence of anemia is 40.5% in children under five, 47.2% at school age, 57.1% in adolescent girls and 50.9% in pregnant women. Anemia is a condition with a blood hemoglobin (hb) level that is lower than normal as a result of the inability of the tissues forming red blood cells to produce to maintain hemoglobin levels at normal levels. Dates are high in carbohydrates so they can provide sufficient energy. Some of the sugar content consists of glucose, fructose and sucrose. According to data from the Hajj health ministry, it was explained that the iron level in dates is also quite high, namely 0.90mg / 100g dates (11% RDA), where iron is a component in the blood to carry oxygen in the blood, to maintain iron balance. in the body, thereby reducing the risk of bleeding in pregnant women. Giving date palm juice has an effect on hemoglobin levels in anemic rats. These results indicate that date juice which is rich in iron can increase hemoglobin levels.